2020
DOI: 10.1016/j.jogoh.2020.101826
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the Covid-19 pandemic among pregnant women in France

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
170
3
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(209 citation statements)
references
References 15 publications
18
170
3
18
Order By: Relevance
“…1); some studies reported data on > 1 pertinent outcome. Of these, there were 52 studies reporting results on obesity prevalence among patients with COVID-19 involving a total of 504,556 cases (8,9,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (Table 2). There was signi cant evidence for heterogeneity across studies in all analyzes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1); some studies reported data on > 1 pertinent outcome. Of these, there were 52 studies reporting results on obesity prevalence among patients with COVID-19 involving a total of 504,556 cases (8,9,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (Table 2). There was signi cant evidence for heterogeneity across studies in all analyzes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The retrieval publications were screened and abstracted if they met the following inclusion criteria: a) Observational studies (cohort, case-control, cross-sectional, case series); b) Studies providing su cient information for the calculation of relative risk (RR) and / or odds ratio (OR), in cases which critical data were not reported in the eligible articles, we contacted authors; c) Studies reporting the prevalence of obesity in COVID-19 patients (primary outcome) and/or data on the association between obesity and following secondary outcomes: COVID-19 and COVID-19 severity (severe COVID-19 was de ned based on international guidelines or hospitalization, ICU (Intensive Care Unit) admission, need for mechanical ventilator, mortality due to COVID-19 or a combination of these) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Duplicates, case reports, reviews, studies with insu cient data after contacting with authors, and abstracts were all excluded, but letters were included.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…2 (Table 1), a figure which is 3.4 times higher than the total number of COVID-19-related maternal deaths reported throughout the rest of the world at the time of writing. [3][4][5][6][7] The current mortality rate is 12.7% in the Brazilian obstetric population, which is also higher than rates reported so far in the literature. 3,4,7 Notably, the mortality rate was higher for cases identified in the postpartum period than during pregnancy, likely reflecting the onset timing of COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 69%
“…6 While some larger studies have examined in detail the medical course of hospitalized COVID-19 positive pregnant patients, few studies have focused on blood-loss and hemorrhage-related outcomes of COVID-19 in pregnancy. [12][13][14][15] One case series found coagulopathy-indicating laboratory markers in two pregnant patients; only one of the patients had a delivery associated with postpartum hemorrhage. 4 Furthermore, while reviews and case reports in nonpregnant populations have reported some severe morbidity and even mortality in COVID-19 associated with bleeding or hemorrhage, [1][2][3][4] there have been very limited data regarding specific laboratory derangements that may be predictive for or associated with bleeding risk related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Most of the limited literature in this field have relied large national cohorts to describe obstetric and surgical morbidity in the setting of COVID-19 infection. [12][13][14][15] These databases necessarily combine results from institutions with varying protocols for hemorrhage risk screening and management. Additionally, multicohort studies are limited by misclassification biases secondary to significant variance in study setting.…”
Section: Discussionmentioning
confidence: 99%